2014
DOI: 10.1177/0883073814539560
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of KCNJ10 Gene Polymorphisms in Childhood Epilepsy

Abstract: The purpose of this study was to investigate the possible association between childhood epilepsy and KCNJ10 gene polymorphisms (rs61822012 and rs2486253). A total of 200 epileptic cases and 200 healthy controls enrolled to this study. Genomic DNAs from the patients and control cases were analyzed by polymerase chain reaction (PCR) and restriction fragment length polymorphism methods. There were significant associations between the G/T genotype of KCNJ10 gene rs2486253 polymorphism in the idiopathic generalized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…Although oK ir 4.1cKO mice did not exhibit alterations in the structure of myelin or progressive disability, these animals died much earlier than control littermates ( Figure 5A ). K ir 4.1 is a risk factor gene for epilepsy ( Bockenhauer et al, 2009 ; Dai et al, 2015 ; Inyushin et al, 2010 ; Lenzen et al, 2005 ; Scholl et al, 2009 ), raising the possibility that K ir 4.1 dysfunction in oligodendrocytes is sufficient to increase seizure susceptibility and induce death. Consistent with this hypothesis, oK ir 4.1cKO mice exhibited occasional seizures and mice that had died were often discovered with limbs extended, suggesting that they had suffered a catastrophic seizure.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although oK ir 4.1cKO mice did not exhibit alterations in the structure of myelin or progressive disability, these animals died much earlier than control littermates ( Figure 5A ). K ir 4.1 is a risk factor gene for epilepsy ( Bockenhauer et al, 2009 ; Dai et al, 2015 ; Inyushin et al, 2010 ; Lenzen et al, 2005 ; Scholl et al, 2009 ), raising the possibility that K ir 4.1 dysfunction in oligodendrocytes is sufficient to increase seizure susceptibility and induce death. Consistent with this hypothesis, oK ir 4.1cKO mice exhibited occasional seizures and mice that had died were often discovered with limbs extended, suggesting that they had suffered a catastrophic seizure.…”
Section: Resultsmentioning
confidence: 99%
“…Several spontaneously arising rodent models of epilepsy were found to have altered K ir 4.1 levels ( Harada et al, 2013 ; Nagao et al, 2013 ), and a single-nucleotide polymorphism in the K ir 4.1 gene ( kcnj10 ) was found to be responsible for differences in seizure susceptibility between C57BL6 and DBA/2 mice ( Ferraro et al, 2004 ; Inyushin et al, 2010 ). In addition, polymorphisms in KCNJ10 are risk factors for epilepsy in humans ( Buono et al, 2004 ; Dai et al, 2015 ; Guo et al, 2015 ; Lenzen et al, 2005 ), and seizures are a prominent component of the human disorder SeSAME/EAST syndrome, which results from loss-of-function mutations in KCNJ10 ( Bockenhauer et al, 2009 ; Scholl et al, 2009 ). It has been assumed that the seizures are primarily caused by astrocyte abnormalities and downstream sequelae.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies showed that loss-of-function mutations of the human gene ( KCNJ10 ) encoding Kir4.1 channels are responsible for the SeSAME/EAST syndrome, an autosomal recessive disorder characterized by seizures, sensorineural deafness, ataxia, intellectual disability and electrolyte imbalance (Bockenhauer et al, 2009; Scholl et al, 2009; Reichold et al, 2010). Genetic variations of KCNJ10 have also been related to epilepsy (Buono et al, 2004; Ferraro et al, 2004; Lenzen et al, 2005; Dai et al, 2015), a group of neurological diseases characterized by seizure disorders. Other diseases associated to Kir4.1 channels include spinocerebellar ataxia (Gilliam et al, 2014), autism (Sicca et al, 2011), Alzheimer disease (Wilcock et al, 2009), and Huntington disease (Tong et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…28 Meanwhile, in a pediatric epilepsy patients group in Japan, the GT genotype of KCNJ10 gene rs2486253 polymorphism also significantly increased the risk for development of idiopathic generalized epilepsy of children. 29 Among a Chinese Han population, Hapmap database shows that rs1130183 are all CC genotypes, with extremely low frequency of T allele, which is not suitable for our SNPs study. Previously, rs6690889 TC and TT genotypes were found to have lower frequencies in genetic generalized epilepsy patients than in healthy controls recruited from southern China by the research of Guo et al Hence, they speculated that potential SNP loci of KCNJ10 may contribute to seizure susceptibility and antiepileptic drug resistance.…”
Section: Discussionmentioning
confidence: 99%